Analysis of the Effect of e-WOM on Brand Loyalty for Skintific Products with Consumer Satisfaction as Mediator - Andaliastari, Nastya; Ananda, Artha Sejati (Journal Research of Social Science, Economics, and Management, 2026)
Skincare has evolved into an essential necessity for consumers of all age groups, as increased awareness of skin health drives greater spending allocation. This study aims to analyze the influence of electronic word of mouth (e-WOM) on brand loyalty in Skintific products with customer satisfaction as a mediating variable. This research is based on the Stimulus–Organism–Response (S-O-R) model, where e-WOM is positioned as a stimulus, customer satisfaction as an organism, and brand loyalty as a response. A quantitative approach with a cross-sectional design was employed in this study, involving 246 respondents who used Skintific products, obtained through the distribution of online questionnaires. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study show that e-WOM has a positive and significant effect on customer satisfaction and brand loyalty. In addition, customer satisfaction has been shown to mediate the relationship between e-WOM and brand loyalty, indicating that positive perceptions of online information can improve the consumer experience while strengthening their commitment to the brand. These findings affirm the importance of digital communication strategies based on consumer reviews in building brand loyalty in the competitive skincare industry, providing practical contributions to industry players in designing more effective marketing strategies through e-WOM optimization and enhancing the customer experience.